Juvenile recurrent parotitis: Report of two cases - Sawant, Sangeeta Priyadarshi (Indian Journal of Child Health, 2014)
Juvenile recurrent parotitis is a recurrent, nonobstructive, and nonsuppurative inflammatory condition of theparotid gland of uncertain etiology in young children. It is characterized by multiple episodes of unilateral orbilateral parotid inflammation over a period of years. Two cases of juvenile recurrent parotitis in a 3-year-oldgirl and a 6-year-old boy are reported. Both presented with multiple episodes of the parotid gland swelling.Investigations for infective etiology, an autoimmune disorder, Sjogren’s syndrome, and immunodeficiency werenegative. Diagnosis was established clinically and confirmed by ultrasound. They were managed symptomatically and recovered in 6-7 days. The parents were counseled about the benign nature of the condition and its resolution by puberty.